Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Far table: Garrick Byers, Chris Marie Brown, Luisa Medina and Patience Milrod; backsides; ?Mendoza, Alice Mendoza, John Joyce and John's wife; close up: Laurie Leifer, Michael Coburn, Herbert Levy, Dora Gonzales and Lloyd Gonzales